Conceptual Metaphors in Selected Song Lyrics of Les Misérables Original Broadway Soundtrack - Lazar, Paskalina Dwi Intan Bui; Bram, Barli (Center of Language and Cultural Studies [CLCS], 2021)
In a musical drama, a good song certainly supports the performance of the musical. When writing lyrics, many songwriters use figurative language to make their songs more lively and meaningful. One of the types of figurative language used is metaphor. This paper aimed to discover the conceptual metaphors in Les Misérables original Broadway soundtrack's selected song lyrics and find the meanings of metaphors found in song lyrics of Les Misérables original Broadway soundtrack. In the data analysis, a qualitative approach was applied to find the literal meanings and metaphorical meanings of the conceptual metaphors. The data were collected from 10 selected songs of Les Misérables' original soundtrack. The results showed that there were 25 conceptual metaphors of 48 lyrics taken from 10 songs. More specifically, 14 conceptual metaphors are classified as structural metaphors, five as orientational metaphors, and six as ontological metaphors in the selected song lyrics.